A novel NGS library preparation method to characterize native termini of fragmented DNA. Issue 8 (29th February 2020) - Harkins, Kelly M; Schaefer, Nathan K; Troll, Christopher J; Rao, Varsha; Kapp, Joshua; Naughton, Colin; Shapiro, Beth; Green, Richard E
Abstract: Biological and chemical DNA fragmentation generates DNA molecules with a variety of termini, including blunt ends and single-stranded overhangs. We have developed a Next Generation Sequencing (NGS) assay, XACTLY, to interrogate the termini of fragmented DNA, information traditionally lost in standard NGS library preparation methods. Here we describe the XACTLY method, showcase its sensitivity and specificity, and demonstrate its utility in in vitro experiments. The XACTLY assay is able to report relative abundances of all lengths and types (5′ and 3′) of single-stranded overhangs, if present, on each DNA fragment with an overall accuracy between 80–90%. In addition, XACTLY retains the sequence of each native DNA molecule after fragmentation and can capture the genomic landscape of cleavage events at single nucleotide resolution. The XACTLY assay can be applied as a novel research and discovery tool for fragmentation analyses and in cell-free DNA.